2010
DOI: 10.1177/0959683609351903
|View full text |Cite
|
Sign up to set email alerts
|

A Holocene record of sea level, vegetation, people and fire from western Tasmania, Australia

Abstract: The analysis of a 10 000 calendar year (cal. ka) pollen record on the west coast of Tasmania has revealed a suite of changes that can be related to sea level, fire and people. Fire-promoted moorland has occupied the site for the entire period and challenges the long-held assumption that rainforest dominated the landscape of western Tasmania through the early to mid Holocene. Changes in wetland taxa and the occurrence of benthic marine diatoms indicate a Holocene sea-level high-stand between 6.3 and 5.8 cal. ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…, 2003) and hiatuses have been identified in all moorland peat sections subject to intensive dating (Macphail et al. , 1999; Fletcher & Thomas, 2007a, 2010). Charcoal peaks in the early Holocene in western Tasmania (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…, 2003) and hiatuses have been identified in all moorland peat sections subject to intensive dating (Macphail et al. , 1999; Fletcher & Thomas, 2007a, 2010). Charcoal peaks in the early Holocene in western Tasmania (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Evaluating the efficacy of the alternative stable state model (Jackson, 1968) or the ‘stable fire cycles’ model of Mount (1979) for south‐west Tasmanian landscapes requires datasets with a high temporal resolution (Petraitis & Latham, 1999), which our study of a few fire events and the distribution of rain forests at a single point in time cannot provide. Recent palaeoecological studies have shown that the pattern of lowland vegetation has remained remarkably stable throughout the Holocene (Fletcher & Thomas, 2007, 2010b), with the authors suggesting the apparent resilience of each vegetation community is the result of fire–vegetation feedbacks that were maintained by Aboriginal burning throughout this period (Fletcher & Thomas, 2010a). Unfortunately, the low spatial resolution of these studies precludes any detailed analysis of the role of environmental variables such as topography in influencing this apparent stability.…”
Section: Discussionmentioning
confidence: 99%
“…The cool, wet climate and low bedrock nutrient status results in extreme oligotrophy that reduces primary productivity and results in remarkably slow rates of change in the vegetation of the region (Bowman and Jackson, 1981). Fire is an important ecological agent in southwest Tasmania (Jackson, 1968;Wood and Bowman, 2012) and human occupation for the past 40,000 years has had a major impact on the vegetation landscape (Bowman, 1998;Cosgrove, 1999;Bowman and Wood, 2009;Thomas et al, 2010;Fletcher and Thomas, 2010a;Fletcher et al, 2014aFletcher et al, , 2014b. Treeless pyrophytic vegetation types dominate the landscape (including species of Melaleuca, Leptospermum and Restionaceae and Gymnoschoenus sphaerocephalus) and pyrophobic arboreal communities (rainforest) are restricted by topography and aspect and the protection those afford from fire (Wood et al, 2011).…”
Section: Southwest Tasmaniamentioning
confidence: 99%